Electrochemical Glucose Biosensors: Whole Cell Microbial and Enzymatic Determination Based on 10-(4H-Dithieno[3, 2-b:2′, 3′-d]Pyrrol-4-yl)Decan-1-Amine Interfaced Glassy Carbon Electrodes. (3rd May 2019) - Cevik, Emre; Cerit, Alaaddin; Tombuloglu, Huseyin; Sabit, Hussein; Yildiz, Huseyin Bekir
Abstract: The fabrication of amperometric biosensors based on whole cell Gluconobacter oxydans DSMZ 2343 ( G. oxydans ) and glucose oxidase (GOx) was performed for the detection of glucose. Glassy carbon electrodes (GCE) were coated with a 10-(4 H -dithiyeno [3, 2-b:2', 3'-d]pyroll-4-il)decan-1-amine (DTP-alkyl-NH2 ) polymer using an electropolymerization method and the formed interface was used to connect the bacteria and the enzyme to the electrode. The transfer of electrons from enzyme to electrode was successfully demonstrated by the biocatalytic activity and unique morphology of the conducting polymer. Characterization of the biosensors was assessed using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and scanning electron microscopy (SEM) analyses. The detection limits of the enzyme and microbial based biosensors for glucose were 0.022 and 0.081 mM, respectively. The broad linear dynamic ranges of the GOx and G. oxydans biosensors were observed to be 0.045–50.0 and 0.19–50.0 mM, respectively. The analytical performances of biosensors were compared according to the following figures of merit: detection limits, limits of quantification, pH and current response time. In addition, to demonstrate the applicability of the biosensors, real-time measurements and recovery studies were evaluated.